Interplay Between Species Traits, Community and Environmental Context Governs Temporal Stability in Riverine Fish Populations - Guido A. Herrera‐R; Julian D. Olden; Pablo A. Tedesco; Lise Comte; Xingli Giam (Ecology Letters, 2026)
Understanding the mechanisms underlying the temporal stability of ecological systems remains a challenge. Although temporal stability in populations is posited to emerge from the interplay between intrinsic and extrinsic factors, the nature of these interactions remains poorly understood. Here, we analysed abundance time‐series for 7912 populations from 287 fish species across 1557 streams spanning multiple biogeographic realms. We evaluated how species traits interact with environmental and biotic contexts to shape temporal stability. Populations were most stable among equilibrium‐strategist species, at higher trophic positions and with lower dispersal abilities. Temporal stability was also greatest near species' thermal and flow niche centers and in less speciose communities, with life‐history traits modulating these effects. Notably, the effects of environmental variability were less pronounced and contingent on species traits. Our findings provide empirical evidence that interspecific trait differences are key determinants of temporal stability, highlighting the value of trait‐based approaches for generalizing biodiversity dynamics.